Hochuekkito can Prevent the Colonization of Methicillin-Resistant Staphylococcus aureus in Upper Respiratory Tract of Acute Stroke Patients - Masakazu Kitahara; Shin Takayama; Shin Takayama; Shin Takayama; Tetsuya Akaishi; Tetsuya Akaishi; Akiko Kikuchi; Akiko Kikuchi; Akiko Kikuchi; Tadashi Ishii; Tadashi Ishii; Tadashi Ishii (Frontiers Media S.A., 2021)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) colonization can lead to MRSA pneumonia or other infections in compromised hosts, and invasive MRSA infections lead to significant morbidity and mortality. The present observational study elucidated whether administration of hochuekkito (HET) can prevent MRSA colonization in the upper respiratory tract and support recovery in acute stroke patients.Methods: In this retrospective, observational study, 73 acute stroke patients admitted to Kenwakai Hospital between April 2007 and December 2019 who did not require emergency surgery during this period were enrolled. Conventional treatment was provided to all patients, depending on their condition, and 7.5 g/day of HET was administered to the patients who could take the medicine via nasogastric tube or orally in three divided doses for three months. Bacterial cultures from laryngeal swabs and sputum were evaluated every week. We evaluated the presence of MRSA infection or another infectious disease within 30 days of admission; modified Rankin Scale scores, which assesses the independent living skills after stroke at three months after admission; and blood biomarkers (white blood cell count, albumin levels, C-reactive protein levels, and hemoglobin levels).Results: In total, 73 patients (HET group, n = 41; non-HET group, n = 32) were enrolled in the study. MRSA detection was significantly less likely in the HET group than in the non-HET group (p = 0.0497). The incidence of infectious diseases was significantly lower in the HET group than in the non-HET group (p = 0.0096), and the modified Rankin Scale score at three months was also significantly lower in the HET group than in the non-HET group (p = 0.033). The white blood cell count, and serum C-reactive protein levels did not differ between those who were treated with HET and those who were not. However, serum albumin and hemoglobin levels improved slightly between month one and month three after admission only in those who were treated with HET.Conclusion: Our results indicate that the administration of HET may contribute to the prevention of MRSA colonization and promote rehabilitation in stroke patients.